PREDICTIVE VALIDITY OF BEHAVIORAL DESPAIR MODELS IN APPRAISING ANTIIMMOBILITY EFFECTS OF ONDANSETRON - AMITABH A KUMAR; PADMA SRAVANI; VISHNU PRIYA (International Journal of Pharma and Bio Sciences, 2014)
Experimental appraisal of antidepressants (ADs) in varied animal models is the need of time. There is a regular hunt for novel models with ease and quick screening of AD activity. As previous studies depict AD effect of ondansetron (OND) in animal models, the study was carried out to compare the efficacy of two behavioral despair models in delineating antidepressant-like effect of OND. OND in tail suspension test (TST) produced significant AD effect at a low dose of 0.25 mg/kg, as depicted by reduction in immobility period of drug-treated mice compared to control group (p<0.05), whereas OND in forced swim test (FST) produced insignificant AD effect at the dose of 0.25 mg/kg as compared to control (p>0.05). Results of our study highlight AD-like activity of OND in TST and FST models of depression, but TST in mice seems to be more sensitive in evaluating the AD like effect of OND.